PENGARUH DEBT TO ASSET RATIO DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN - Fauji, Fauji; Nurdiansyah, Dian Hakip (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2025)
The rapid development of technology presents a significant challenge for entities in Indonesia. This is primarily due to the expectation that technological advancements should be accompanied by an increase in human resource capabilities. In addition, there are adverse effects that may arise, particularly for entities within the media industry sub-sector. One such impact is the growing public interest in video streaming services, which may affect the Firm Value. This study aims to examine the effect of the Debt to Asset Ratio (DAR) and the Debt to Equity Ratio (DER) on Firm Value, both partially and simultaneously. The research focuses on DAR and DER within media industry sub-sector entities to assess whether the assets and equity owned by these entities are sufficient to meet their liabilities, and whether increases in these financial ratios have an impact on Firm Value. A quantitative research method was employed, with the population and sample comprising entities from the media industry sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The results of this study indicate that both the Debt to Asset Ratio and the Debt to Equity Ratio have a significant influence on Firm Value, whether measured individually (partially) or collectively (simultaneously).